The Struggle of the Former Spanish Forced Workers of the Third Reich for recognition as victims of Nazism (1956-1972) - Muñoz Sánchez, Antonio (Hispania Nova, 2021)
The text deals with a little known chapter of the Spanish Civil War exile: the struggle that thousands of Spaniards forced to work for the Germans during World War II put forward years later to obtain compensation from the FRG as victims of Nazism. It begins by tracing the main lines of the history of Spanish forced laborers in Hitler's Europe. It continues with a brief description of the policy of compensation for the victims of the Third Reich promoted by Konrad Adenauer's government. Finally, it dissects, on the basis of archival sources, the long and complex administrative and judicial process that ended up leading those Spanish Republicans to be recognized, in the same way as their comrades deported to Mauthausen, as persecuted of Nazism and to obtain German compensation for it.
Keywords: World War II; spanish republican exile; forced labor; justice; memory